2020
DOI: 10.1038/s41598-020-58806-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profiles of the Tryptophan-Kynurenine Pathway in the high risk subjects of major depressive disorder

Abstract: Previous reports have shown that during chronic inflammation, the tryptophan (TRP)-kynurenine (KYN) pathway plays a pivotal role in the onset of depression. The aim of this study was to investigate the characteristics of the serum TRP-KYN pathway metabolite profile in high-risk subjects of major depressive disorder (HRMDD) defined by depression scores. The concentrations of TRP-KYN pathway metabolites {TRP, KYN, 3-hydroxyanthranilic acid (3HAA), 3-hydroxykynurenine (3HK), kynurenic acid (KYNA) and anthranilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 44 publications
8
30
0
1
Order By: Relevance
“…In a recent study, Dong et al reported an increase in serum KYN in AML patients compared to healthy controls [10]; this is in good agreement with the increase in serum KYN that we observed in all hematological categories. In accordance with previous reports [9], the levels of serum TRP in patients with hematological malignant tumors were lower in females than in males. However, IDO activity showed no differences between men and women.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a recent study, Dong et al reported an increase in serum KYN in AML patients compared to healthy controls [10]; this is in good agreement with the increase in serum KYN that we observed in all hematological categories. In accordance with previous reports [9], the levels of serum TRP in patients with hematological malignant tumors were lower in females than in males. However, IDO activity showed no differences between men and women.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of AHR by KYN on dendritic cells inhibits dendritic cell maturation and immune surveillance, thereby promoting tumor survival [11]. Our results show that KYN and AA concentrations increased, while 3-HAA concentration decreased, in hematological malignant tumors compared to our previous data on healthy volunteers [9]. Moreover, 3-HAA inhibits nitric oxide synthase in macrophages and shows antioxidant activity in response to the local oxidative environment, thus regulating the tissue oxidative status [7].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Though tryptophan metabolism was not suggested in our analysis, one metabolite in its pathway, anthranilic acid, was signi cantly associated with anxiety levels in UC patients. Anthranilic acid is a secondary metabolite of kynurenine, and is reported to be a biochemical "warning sign" of early-stage depression [37] and a marker for in ammation assessment in the brain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Classical conceptualizations of stress and depression have attributed such changes to the associated decrease in brain serotonin as well as to the neuroregulatory effects of kynurenine pathway products, such kynurenic acid and quinolinic acid [ 38 ]. However, there is a growing appreciation that even classical psychiatric disorders—such as depression [ 39 , 40 ], anxiety [ 41 ], and schizophrenia [ 42 ]—are powerfully determined by alterations in the kynurenine pathway and the AhR regulation of the immune system. The role of neuronal activity in mediating stress/depression has now shifted to viewing neuronal activity more as a form of ‘immune-to-immune’ communication [ 43 ].…”
Section: Sars-cov-2 Entry and Pathophysiologymentioning
confidence: 99%